(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The crude methanol extract of leaves of Polygonum glabrum Willd and its Kupchan fractions were screened for cytotoxic, membrane stabilizing and thrombolytic activities. Among all fractions, the crude methanol extract showed significant cytotoxic activity having LC50 value 0.74 ± 0.045 ?g/ml. Moreover, in hypotonic solution- and heat- induced conditions, the crude methanol extract inhibited hemolysis of human erythrocyte by 79.21 ± 0.44% and 84.87±0.23%, respectively as compared to 71.9 ± 0.73% and 42.12 ± 0.37% demonstrated by the standard acetyl salicylic acid. On the other hand, in thrombolytic activity assay the methanol extract demonstrated highest clot lysis value of 35.17 ± 0.42%. DOI: http://dx.doi.org/10.3329/bpj.v17i2.22341 Bangladesh Pharmaceutical Journal 17(2): 202-204, 2014